Reflections and the way forward - Ahmad, Abdul Razaq; Chang, Da Wan; Ismail, Russayani; Yew, Meng Lai; Ayub, Zainal Amin (Springer, 2016)
This book presented case studies of six states from the Middle East and North Africa (MENA).The rich narrative in terms of their higher education as well as their political, security, socioeconomic and legal framework has illustrated many important themes and patterns in understanding these countries and the MENA region, as a whole.This concluding chapter identifies and summarises the common key themes that serve as both challenges and/or opportunities for the selected countries in promoting their respective and the region’s higher education development agenda.It also suggests the areas of (re)alignment required and proposes the way forward for the MENA region to fully realise its higher education potentials.